7u+7v-2(7u-6v)=

Simple and best practice solution for 7u+7v-2(7u-6v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7u+7v-2(7u-6v)= equation:


Simplifying
7u + 7v + -2(7u + -6v) = 0
7u + 7v + (7u * -2 + -6v * -2) = 0
7u + 7v + (-14u + 12v) = 0

Reorder the terms:
7u + -14u + 7v + 12v = 0

Combine like terms: 7u + -14u = -7u
-7u + 7v + 12v = 0

Combine like terms: 7v + 12v = 19v
-7u + 19v = 0

Solving
-7u + 19v = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-19v' to each side of the equation.
-7u + 19v + -19v = 0 + -19v

Combine like terms: 19v + -19v = 0
-7u + 0 = 0 + -19v
-7u = 0 + -19v
Remove the zero:
-7u = -19v

Divide each side by '-7'.
u = 2.714285714v

Simplifying
u = 2.714285714v

See similar equations:

| 3.0x+50.3=26.7-7.9x | | 2x+y+x=180 | | 2.7x+0.81=1.62 | | 2y+3y=20 | | 2(3a-9)=-10(a-1) | | fraction= | | p+8/3=2 | | (3x-8)(2-x)=0 | | x-7=2(2x-4) | | 2.7x+0.81=19 | | 5(8c+5)= | | 7(b-8)= | | 230+5*12= | | e/6-4=-2 | | 800-50X= | | 10x-8x+6-8= | | -8p=20 | | 40-(-5)= | | 10x-8x+6=8 | | 4688x+7=167 | | 4x+7=167 | | 3+7i-3i-4= | | 10-(r+7)=2(r+3) | | 5(.2-3)=5(60) | | 5x+72=8x-12 | | .2-3=60 | | 6x+11x-3=48 | | 12d-8d= | | 9+2x+3x=24 | | 6(b-4)-5(b+4)=6 | | 12c-8c= | | X=8z-3y |

Equations solver categories